Designing digital storytelling books for TPACK development of Indonesian pre-service ELT teachers - Signori, Tifani Yuris; Drajati, Nur Arifah; Putra, Kristian Adi (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2024)
In today's educational system, the need for teachers to acquire technological, pedagogical, and content knowledge (TPACK) has already become a mainstream transformation. Therefore, it is necessary to find a suitable strategy and approach to develop pre-service ELT teachers’ TPACK, in which one of them is actively engaging them in the design of technology-enhanced learning. This study sought to investigate Indonesian pre-service ELT teachers’ TPACK level development after designing digital storytelling book. Narrative inquiry was adopted in this research. The data were obtained from the pre- service ELT teachers’ reflective notes and semi-structured interviews. The findings of the study show that all participants are in the TPACK level of “accepting”. In the level of accepting, pre-service teachers form a favorable attitude toward teaching and learning English with digital storytelling. The implication derived from this study is that it is necessary to carefully design a project in teacher education program that can improve the pre-service teachers' TPACK level.